Valuation de empresas pelo critério da intangibilidade de seus ativos: um estudo de caso em uma companhia de serviços ferroviários - Coelho, João Lucas Marques (2021)
The theme of this study is about the intangibility of business assets and their valuation in a stateowned company, with the objective of measuring the valuation of the railway company using the criterion of the intangibility of its assets. In line with the theoretical contribution, the valuation will be treated based on a systemic view of the company's value and the criterion used will be the intangibility of its assets. Composed of the practice, the decision-making procedures of the entity will be analyzed. A case study was carried out in the mixed state company, provider of railway logistics services, called Estrada de Ferro Paraná Oeste SA, referred to as Ferroeste. This case study research is characterized with a qualitative and quantitative approach. The method to find a company's intangible value is important for validation and recognition, since its results are increasingly decisive for decision making. Among several theoretical models and tools designed to find the valuation of an organization, the systematization proposed by Hoss (2018) was taken into account. The necessary data procedures to be collected will be separated into qualitative and quantitative variables. First, the qualitative analysis, through the financial statements, the investment plans and the evaluation of the accounting indexes. Then, the qualitative ones, using the Survey and Delphi technique. In this sense, the valuation of intangible assets that can be identified is important for their management within the state-owned company, as it allows defining the management strategy for each key intangible asset and identifying the economic advantages provided and the perspectives of possible impacts in decision-making.